Peran Personalia Sekolah dalam Pelaksanaan Layanan Bimbingan dan Konseling - as ad, moch khakam (Universitas Negeri Semarang, 2017)
Based on the phenomenon of inadequacy from the role of school personnel in guidance and counseling services in Senior High School 1 Kedungwuni. The aim of this research is to get the empirical data of school personnel role in guidance and counseling services. It is a survey research. The population of the research is personnel schools that is a school principal , the teacher coordinators for guidance and counseling and all of homeroom teachers in All senior high school Pekalongan. Two Kinds of Sampling technique were used in this research which were saturated sampling for headmaster and guidance and counseling teacher, and the second was cluster proportional random sampling to determine the amount of homeroom teachers. The result of the research showed 61,56% and it was within the criteria “good enough’, it means that ever personnel understood their role in giving the guidance and counseling so, it helps the students to solve their problem and develop their potential. It was hoped that every school personal understand.